Analisis Prinsip-Prinsip Esensial Dalam Meningkatkan Motivasi Siswa Melalui Pendekatan Berdasarkan Konsep Rothwal - Qurniati, Alif; Alfisyahrani, Aura; Cahyani, Ilhimimah; Savitri, Malinda Dewi; Sutarto, Sutarto (Jurnal Ilmiah Wahana Pendidikan, 2024)
Principles are the basis for learning efforts, are the most important model for achieving satisfactory results for both students and teachers, and are the most important model for achieving satisfactory results for both students and teachers, and are desired so that the learning process can be successful. Learning is the process of changing behavior from someone we don't know to someone we know. Defining the principle of self-directed learning: creating and producing respectful and enjoyable study and learning activities. As a basis, you need to know learning principles and theories. These principles are used by both students and teachers as a basis for learning efforts to achieve the desired goals . Motivation begins with the word "motivation" and can be interpreted as follows: When we are active when doing something, this is felt as a fairly urgent need to achieve a goal. Motivation is an individual's internal drive to carry out an action in a certain way in accordance with planned goals. Motivation is related to the goals to be achieved. Hamzah B concluded that motivation is a force that exists within a person and causes him to act or act. Motivation and learning are two things that influence each other.. With Rothwal's learning principles, every teacher is advised to be able to create learning strategies that are fun and not boring.